Obama his story - Waite, Jacob; Smith, Guy ([Australia] : BBC, 2009)
In the year that America inaugurates its first black president, this timely film takes a look at the life of BArack Obama to see just how he rose to the position of arguably the most important government leader in the world.
Executive producer, Samantha Anstiss.
DVD format.
Keywords: Obama, Barack; Presidents -- United States -- Biography